First Cousin Marriages and the Risk of Childhood-Onset Vitiligo: Exploring the Genetic Background: A Cross-Sectional Study - Molla A; Alayoubi AM; Jannadi R (Dove Medical Press, 2024)
Amr Molla,1 Abdulfatah M Alayoubi,2 Raed Jannadi3 1Department of Medicine, College of Medicine, Taibah University, Madinah, Saudi Arabia; 2Department of Basic Medical Sciences, College of Medicine, Taibah University, Madinah, Saudi Arabia; 3Department of Family & Community Medicine &, Medical Education, College of Medicine, Taibah University, Madinah, Saudi ArabiaCorrespondence: Amr Molla, Universities Road, P.O. Box: 344, Taibah, Madinah, 42353, Saudi Arabia, Tel +966504342992, Email amolla@taibahu.edu.saBackground: Vitiligo, a condition characterized by depigmented skin, has been observed to have a higher incidence in patients with a family history of the disease. This study investigates the relationship between parental consanguinity, family medical history, and the onset of childhood vitiligo, hypothesizing that genetic factors play a significant role.Methods: A cross-sectional study was conducted involving 382 people diagnosed with vitiligo in Saudi Arabia. The study assessed the prevalence of parental consanguinity and its correlation with the disease's onset, employing statistical analysis to evaluate the data collected through medical records and family history questionnaires.Results: The findings reveal a significant association between parental consanguinity, particularly among first cousins, and the incidence of childhood-onset vitiligo. Additionally, a notable correlation was found between family medical history and the onset of the condition, with familial vitiligo being more prevalent in patients with adult-onset vitiligo.Conclusion: This study underscores the critical role of genetic predispositions in the development of childhood-onset vitiligo, highlighting the influence of parental consanguinity. The results advocate for increased awareness and screening in populations with high rates of consanguinity to facilitate early detection and management of vitiligo. Future research should focus on exploring the genetic mechanisms underlying this association to develop targeted interventions.Keywords: parental consanguinity, childhood-onset vitiligo, genetic factors, familial vitiligo, Saudi Arabia, cross-sectional study